Research and design for a storage liquid refrigerator considering the characteristics of energy storage batteries - Zhou, Xianwei; Liu, Chuncheng; Qian, Yi; Bi, Zhenyu; Yang, Mo (Frontiers in Energy Research, 2024)
At present, energy storage in industrial and commercial scenarios has problems such as poor protection levels, flexible deployment, and poor battery performance. Aiming at the pain points and storage application scenarios of industrial and commercial energy, this paper proposes liquid cooling solutions. In this paper, the box structure was first studied to optimize the structure, and based on the liquid cooling technology route, the realization of an industrial and commercial energy storage thermal management scheme for the integrated cabinet was studied to ensure that the temperature between the cabinets was consistent and reduce the system capacity loss caused by the liquid-cooled battery module was inconsistent. The industrial and commercial energy storage integrated cabinet comprehensively considers the flexible deployment of the system, enhances the protection level of the cabinet, and the structural strength of the cabinet, and improves the temperature balance characteristics of the battery module in the cabinet.